Cu(II)-triggered release of paclitaxel from a supramolecular complex - Sun, Tao; Yan, Hui; Xing, Pengyao; Su, Jie; Li, Shangyang; Hao, Aiyou (Supramolecular chemistry, 2013)
The research on the stimuli-responsive property of biological or synthetic macromolecules in a wide range of scientific fields is a crucial subject for the achievements of the targeted drug release and the precise control of the functions of the supramolecules at a molecular level. We used an anthraquinone-functioned cyclodextrin (1) bridged by an aza-arm to solubilise paclitaxel (PTX) by forming a supramolecular complex (1/PTX). The possible inclusion mode was given based on the experimental results of ultraviolet-visible spectroscopy, Fourier transform infrared, X-ray diffraction, fluorescence spectra, nuclear magnetic resonance, transmission electron microscope, scanning electron microscope and dynamic light scattering characterisations. The controlled release of PTX can be achieved by adding Cu 2+ to the solution. This study provides useful references in developing stimuli-responsive drug-carrying and drug-releasing materials.